Effect of Turbidity on Dominance of Buoyant Cyanobacterium, Microcystis wesenbergii against Non-buoyant Phytoplankton − A Mixed Culture Approach - Kishimoto, Naoyuki; Suzuki, Kei (Journal of Water and Environment Technology, 2025)
Cyanobacterial blooms often cause water treatment disturbance problems such as unfavorable odor and taste in tap water and leakage from filter beds. It has been pointed out that blooming cyanobacteria are less susceptible to photoinhibition due to their buoyant nature, which may give them an advantage in light competition against non-buoyant phytoplankton in turbid environments. However, such indications are based on field observations, and there is no study that have demonstrated the superiority of blooming cyanobacteria in turbid environments through culture experiments. In this study, we conducted static mixed cultures of a buoyant cyanobacterium, Microcystis wesenbergii, and a non-buoyant phytoplankton, Staurastrum dorsidentiferum, isolated from Lake Biwa and evaluated the effect of turbidity on the dominance of M. wesenbergii. Although M. wesenbergii was inhibited by turbidity of 100 kaolin turbidity unit (inhibition rate: 47–49%), the inhibition rate was lower than that of S. dorsidentiferum (inhibition rate: 77%). Moreover, the mixed culture did not inhibit the growth of M. wesenbergii. On the other hand, S. dorsidentiferum was significantly inhibited by mixed culture (inhibition rate: 78%). Thus, experimental results demonstrated that M. wesenbergii is more likely to dominate over non-buoyant phytoplankton due to the shading effects of turbidity and surface accumulation.